(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe several clinical and paraclinical characteristics related to the indication for induction of labor and to evaluate the outcomes of labor induction using a modified double‑balloon Foley catheter at the 103 Military Hospital. Research methods: A cross‑sectional descriptive study was conducted on 68 pregnant women who underwent labor induction with a modified double‑balloon Foley catheter at the 103 Military Hospital from April 2023 to March 2026. Results: The mean maternal age was 28.1 ± 5.7 years; mean BMI was 26.6 ± 3.1 kg/m²; and mean gestational age was 39.2 ± 0.8 weeks. The success rate of labor induction was 92.6%, with an average Bishop score increase of 3.7 ± 1 points after balloon placement (p < 0.001). The overall vaginal delivery rate was 79.4%, with 84.1% in the successful induction group. Complication rates were low, including infection (4.4%) and uterine tachysystole (1.5%); no cases of premature rupture of membranes or fetal distress during balloon placement were recorded. Conclusion: The modified double‑balloon Foley catheter is highly effective in cervical ripening and facilitating vaginal delivery, with a success rate of 92.6% and a favorable safety profile. This method is suitable for implementation in lower‑level healthcare facilities due to its low cost, ease of use, and minimal complications.